Permeability Prediction of Un-Cored Intervals Using FZI Method and Matrix Density Grouping Method: A Case Study of Abughirab Field/Asmari FM., Iraq - B. Alsinbili, Mohammed; N. Aljawad, Sameer; Awni Aldalawy, Ammar (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
Knowledge of permeability is critical for developing an effective reservoir description. Permeability data may be calculated from well tests, cores and logs. Normally, using well log data to derive estimates of permeability is the lowest cost method. This paper will focus on the evaluation of formation permeability in un-cored intervals for Abughirab field/Asmari reservoir in Iraq from core and well log data. Hydraulic flow unit (HFU) concept is strongly related to the flow zone indicator (FZI) which is a function of the reservoir quality index (RQI). Both measures are based on porosity and permeability of cores. It is assumed that samples with similar FZI values belong to the same HFU. A generated method is also used to calculate permeability in un-cored zones depending on matrix density grouping, where each group has its own permeability-porosity correlation. After applying the both methods and correlating the calculated permeability with the core permeability data it revealed that matrix density grouping is the best method to calculate permeability in un-cored zones and it is better than FZI method in this field, then the estimated permeability is distributed through the members of Asmari reservoir in Abughirab field and it is concluded that permeability in this field is generally increases toward south culmination of Abughirab field.